Spectinomycin resistance in Lysobacter enzymogenes is due to its rRNA target but also relies on cell-wall recycling and purine biosynthesis - Yu, Menghao; Zhao, Youfu (Frontiers in Microbiology, 2022)
Resistance to spectinomycin emerged after widely used for treatment of gonorrhea. Previous studies revealed that Lysobacter enzymogenes strain C3 (LeC3) exhibited elevated level of intrinsic resistance to spectinomycin. In this study, we screened a Tn5 transposon mutant library of LeC3 to elucidate the underlying molecular mechanisms of spectinomycin resistance. Insertion sites in 15 out of 19 mutants recovered with decreased spectinomycin resistance were located on two ribosomal RNA operons at different loci, indicating the pivotal role of ribosomal RNAs in conferring spectinomycin resistance in L. enzymogenes. The other mutants harbored mutations in the tuf, rpoD, mltB, and purB genes. Among them, the tuf and rpoD genes respectively encode a translation elongation factor Tu and an RNA polymerase primary sigma factor. They both contribute to protein biosynthesis, where ribosomal RNAs play essential roles. The mltB gene, whose product is involved in cell-wall recycling, was not only associated with resistance against spectinomycin, but also conferred resistance to osmotic stress and ampicillin. In addition, mutation of the purB gene, for which its product is involved in the biosynthesis of inosine and adenosine monophosphates, led to decreased spectinomycin resistance. Addition of exogenous adenine at lower concentration in medium restored the growth deficiency in the purB mutant and increased bacterial resistance to spectinomycin. These results suggest that while cell-wall recycling and purine biosynthesis might contribute to spectinomycin resistance, target rRNAs play critical role in spectinomycin resistance in L. enzymogenes.